Investigation of wear behavior of cutting tool insert for ti-alloy machining using carbon coated with sic sandblasting and hf acid pretreatment - Mohd Izul Aslam, Mohd Khalit (2012)
In machining process, pretreatment of cutting tool surface helped to increase wear resistance of cutting tool. The tool insert used was carbon coated with Hydrofluoric acid (HF) and sand blasting pretreatment, while the machining workpiece was Titanium alloy. Sandblasting was conducted using Silicon Carbide (SiC) particles with 300 grit size. Carbon coating was deposited on the tool insert substrates by using Physical Vapor Deposition (PVD) technique. Morphological observation was conducted using optical microscope to observe the micrographs of tool insert surface in as-received condition and after pretreatment and to measure length of flank wear on the substrate after machining titanium. Parameters used for machining were cutting speed of 100 m/min, depth cut of 0.25 mm and feed rate of 0.1 mm/rev. The substrate surface after coating by different surface pretreatment was measured using Vickers Hardness machine. From the morphological observation, the as-received micrograph has a continuous 45° direction from the horizontal line. Sandblasted substrate showed white spots on the tool insert surface. Surface pretreatment combination with Hydrofluoric acid showed a non-uniform surface with a peak and valley image. Alumina coated with sand blast and hydrofluoric acid pretreatment was found to increase wear resistance by having the shortest wear length of 0.336 mm after machining a titanium alloy rod.